2014
DOI: 10.1016/j.celrep.2014.01.037
|View full text |Cite
|
Sign up to set email alerts
|

RNA-DNA Differences Are Generated in Human Cells within Seconds after RNA Exits Polymerase II

Abstract: Summary RNA sequences are expected to be identical to their corresponding DNA sequences. Here, we found all 12 types of RNA-DNA sequence differences (RDDs) in nascent RNA. Our results show that RDDs begin to occur in RNA chains about 55 nucleotides from the RNA polymerase II (Pol II) active site. These RDDs occur so soon after transcription that they are incompatible with known deaminase-mediated RNA editing mechanisms. Moreover, the 55-nucleotide delay in appearance indicates they do not arise during RNA synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 56 publications
1
51
0
Order By: Relevance
“…Altogether, we identified about 80,000 to approximately 367,000 editing sites per fraction, with an average of 83% comprising A-to-I and C-to-U types (Supplemental Table S2). It should be noted that ChA − had the most non-A-to-G or non-Cto-T types, which may reflect existence of unknown biology (Wang et al 2014). Among all the A-to-G sites identified (440,821 in total), 64% and 75% were included in the RADAR (Ramaswami and Li 2014) and REDIportal (Picardi et al 2017) databases, respectively.…”
Section: Subcellular Rna-seq and Rna Editingmentioning
confidence: 99%
“…Altogether, we identified about 80,000 to approximately 367,000 editing sites per fraction, with an average of 83% comprising A-to-I and C-to-U types (Supplemental Table S2). It should be noted that ChA − had the most non-A-to-G or non-Cto-T types, which may reflect existence of unknown biology (Wang et al 2014). Among all the A-to-G sites identified (440,821 in total), 64% and 75% were included in the RADAR (Ramaswami and Li 2014) and REDIportal (Picardi et al 2017) databases, respectively.…”
Section: Subcellular Rna-seq and Rna Editingmentioning
confidence: 99%
“…Because RDDs are found so soon after transcription, we posited that R-loops that often occur outside of the polymerase complex may be involved in RDD formation. Results from studying human cells with a gain-of-function mutation in senataxin (L389S) that leads to juvenile amyotrophic lateral sclerosis showed lower RDD frequency, consistent with the involvement of R-loops (Wang et al 2014).…”
Section: Rdds Are Dependent On R-loop Formationmentioning
confidence: 94%
“…Previously, we showed RDDs do not arise during RNA synthesis by RNA Polymerase II nor as a direct consequence of incorporation of modified bases; rather, we showed that RDDs begin to occur in nascent RNA chains ∼55 nt from the RNA Polymerase II active site (Wang et al 2014). Because RDDs are found so soon after transcription, we posited that R-loops that often occur outside of the polymerase complex may be involved in RDD formation.…”
Section: Rdds Are Dependent On R-loop Formationmentioning
confidence: 98%
See 2 more Smart Citations